2013
DOI: 10.2134/agronj2012.0447
|View full text |Cite
|
Sign up to set email alerts
|

In‐Season Nitrogen Effects on Organic Hard Red Winter Wheat Yield and Quality

Abstract: Ensuring adequate available N for grain protein development is a primary challenge for organic production of winter bread wheat (Triticum aestivum L.). Topdressing organic wheat in‐season may improve grain yield and quality. The objective of this study was to determine if supplemental N topdressing at key wheat developmental stages would improve organic hard red winter wheat yield and protein concentrations. Field experiments were conducted over 4 site‐years from 2009 to 2011 in Maine and Vermont, using the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
(44 reference statements)
3
25
1
Order By: Relevance
“…These results are congruent with others who have found that applications at the pre-plant timing alone do not supply an adequate amount of late-season available N to enhance CP in winter wheat [3,45]. At the majority of site-years, it was possible that the amount or timing of mineralization from the organic N fraction of manure was insufficient to support protein production.…”
Section: Nitrogen Treatment Effectssupporting
confidence: 87%
See 4 more Smart Citations
“…These results are congruent with others who have found that applications at the pre-plant timing alone do not supply an adequate amount of late-season available N to enhance CP in winter wheat [3,45]. At the majority of site-years, it was possible that the amount or timing of mineralization from the organic N fraction of manure was insufficient to support protein production.…”
Section: Nitrogen Treatment Effectssupporting
confidence: 87%
“…The timing of supplemental N applied in the PP L + T1 39 and PP L + T2 39 treatments had no influence on yield and CP results likely because the applications were too close in time to cause differences. The application at T2 was relatively early compared to other studies that showed topdress applied later, at flag leaf (GS39) and boot (GS45), were more effective at increasing CP than the T1 application [3].…”
Section: Nitrogen Treatment Effectsmentioning
confidence: 70%
See 3 more Smart Citations